2018
DOI: 10.1136/bmjopen-2017-020290
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in UK South Asians: a scoping review of the literature

Abstract: ObjectiveOver 850 000 people live with dementia in the UK. A proportion of these people are South Asians, who make up over 5% of the total UK population. Little is known about the prevalence, experience and treatment of dementia in the UK South Asian population. The aim of this scoping review is to identify dementia studies conducted in the UK South Asian population to highlight gaps in the literature which need to be addressed in future research.MethodDatabases were systematically searched using a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…There was an overwhelming belief from the caregivers that Pakistani people in general had little or no awareness of dementia. These findings are in line with South Asians living in the UK who have shown to have less basic knowledge about dementia than their White-British counterparts (Blakemore et al, 2018). Also, this supports previous findings from the study of caregivers of people with dementia in Rawalpindi/Islamabad, Pakistan, who showed very little or no knowledge of dementia (Qadir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…There was an overwhelming belief from the caregivers that Pakistani people in general had little or no awareness of dementia. These findings are in line with South Asians living in the UK who have shown to have less basic knowledge about dementia than their White-British counterparts (Blakemore et al, 2018). Also, this supports previous findings from the study of caregivers of people with dementia in Rawalpindi/Islamabad, Pakistan, who showed very little or no knowledge of dementia (Qadir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…However, it is also possible that there was under-reporting of dementia symptoms10 18 in people from BAME communities due to stigma or cultural reasons. This could also be due to delay in accessing healthcare services by members of BAME communities unless they felt it was severe,19 or clinicians not recognising symptoms of dementia in BAME groups due to language barriers, or due to more family and community support which lead to delay in diagnosis of dementia 20. Hence, actual rates might be higher for those belonging to Black or South Asian ethnic groups than our findings.…”
Section: Discussionmentioning
confidence: 59%
“…Previous qualitative studies have interviewed UK family carers for people with dementia from South Asian ethnic groups. Attitudes towards caring as natural, a continuation of family relationships, virtuous, and expected predominate in their accounts and of those of people living with dementia (Blakemore et al, 2018;Lawrence, Murray, Samsi, & Banerjee, 2008;Lawrence, Samsi, Banerjee, Morgan, & Murray, 2011;Mukadam, Cooper, Basit, & Livingston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Stigma, fear and mistrust of formal services have been cited as possible explanations for the low rate of help-seeking from formal services reported in South Asian, and other minority ethnic communities (Blakemore et al, 2018). Fear of a move to long-term care may also prevent minority ethnic families or individuals with dementia from seeking help from formal services (Blakemore et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation